1998
DOI: 10.1093/carcin/19.11.1939
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effects of nimesulide, a selective inhibitor of cyclooxygenase-2, on azoxymethane-induced colon carcinogenesis in mice

Abstract: The effects of nimesulide, a selective inhibitor of cyclooxygenase-2 (COX-2) on azoxymethane (AOM)-induced colon carcinogenesis were investigated in mice. AOM at a dose of 10 mg/kg body wt was administered to male ICR mice once a week for 6 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
64
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 22 publications
3
64
0
Order By: Relevance
“…It has been reported that nimesulide, a cyclooxygenase-2 selective inhibitor, showed a remarkable suppressive effect on rodent carcinogenesis but the mechanisms were not identified (5).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that nimesulide, a cyclooxygenase-2 selective inhibitor, showed a remarkable suppressive effect on rodent carcinogenesis but the mechanisms were not identified (5).…”
Section: Introductionmentioning
confidence: 99%
“…This supporting evidence includes the observation that COX isoenzymes are overexpressed in colorectal adenomas and tumors (74 -82). Targeted deletion of the COX-2 gene prevents CRC in animals, and celecoxib as well as other selective COX-2 inhibitors (e.g., JTE-522, NS-398, the tricyclic methyl sulfone derivative MF tricyclic, nimesulide, and rofecoxib) are also effective in preclinical models (83)(84)(85)(86)(87)(88)(89)(90)(91) The Subpart H approval was based on a randomized, double-blind, placebo-controlled study of 83 FAP patients in which 400 mg twice daily celecoxib for 6 months significantly reduced adenoma number by 28% [P Ï­ 0.003 compared with the 4.5% reduction with placebo (100)]. In addition, this celecoxib dose significantly reduced adenoma burden (the sum of adenoma diameters) by 30.7% (P Ï­ 0.001 compared with the 4.9% reduction with placebo).…”
Section: Celecoxib Celecoxib Has a Known Molecular Target [Cyclooxygmentioning
confidence: 99%
“…Doses were selected on the basis of previous experimental results for mice or rats. 19,20,22 Groups 4 and 5, consisting of 10 animals each, were fed a diet supplemented with nimesulide 400 or 0 ppm, respectively, without prior initiation. Hamsters were observed daily and weighed once every 4 weeks.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…4 It is now clear that COX-2 is an inducible immediate early gene, 11 involved not only in inflammation and cell proliferation 11 but also in differentiation, 12 apoptosis, 13 metastasis, 14 immunologic surveillance 15 and angiogenesis. 16 Nimesulide, a preferential COX-2 inhibitor of nonsteroidal antiinflammatory drugs (NSAIDs), 17 inhibits chemically induced colon, 18,19 mammary, 20 tongue 21 and urinary bladder 22 carcinogenesis in rats. However, it is still important to examine the modifying effects of nimesulide on pancreatic carcinogenesis because the postinitiation and promotion stages are supposed to be organspecific.…”
mentioning
confidence: 99%